Kehujahan Kias dalam Rukhsah Syar’iyyah: Blasphemy of Metaphor in Rukhsah Syar'iyyah - Rahmat, Rahmat; Sirajuddin, Sirajuddin; Sabda, Sabda (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
This research aims to find out the blasphemy of kias in rukhsah syar'iyyah, and to find out examples of the application of kias in rukhsah syar'iyyah. This research includes library research using a normative approach method. The data were analyzed using deductive and descriptive qualitative methods. The research results found are as follows: A number of ulama from the Mālikiyah, Syāfi'iyah, and Hanābilah schools of thought allow the use of kias in rukhsah syar'iyyah with the requirement that the pillars and conditions are met. Meanwhile, the Hanafiyah school of thought rejects the use of kias in rukhsah syar'iyyah because rukhsah is a legal provision whose arguments are clear from both the Al-Qur'an and the Sunnah, so kias does not apply in this case. The two actualizations of the application of kias in rukhsah syar'iyyah include examples: istinja using a figurative tissue on a stone, wiping the figurative imamah over wiping shoes, wiping the hijab figuratively over wiping the imamah, wiping figurative socks over wiping shoes, combining two prayers for those who stay because they are afraid allusion to the plural of prayers at 'Arafah and Muzdalifah, and plural prayers because of desire or a figurative work for the plural of prayers at Árafah and Muzdalifah. After examining the arguments from the jumhur ulama and the Hanafiyah school of thought, the opinion of the jumhur ulama which allows the use of kias in rukhsah syar'iyyah is stronger because the opinion of the Hanafiyah school of thought is weak and even some of their followers also refute the opinion which does not allow the use of kias in rukhsah syar'iyyah.